Determinants of Poor Sleep Quality During the COVID-19 Pandemic Among Women Attending Antenatal Care Services at the Health Facilities of Debre Berhan Town, Ethiopia: An Institutional-Based Cross-Sectional Study - Amare, Nakachew Sewnet; Chekol, Basazinew; Aemro, Agazhe (Frontiers in Psychiatry, 2022)
Background: Women’s ability to get sleep can be affected by pregnancy-related hormonal changes or other external stressful situations like the coronavirus disease 2019 (COVID-19). Objective: The objective of this study was to assess the proportion of poor sleep quality during the COVID-19 pandemic and its determinants among pregnant women attending antenatal care (ANC) services. Methods: An institutional-based cross-sectional study was conducted among 423 women attending ANC services at the health facilities in Debre Berhan Town, Ethiopia, from May to June 2020. A systematic random sampling technique was used to select the required samples. The tool consisted of questions that assessed 1) socio-demographic characteristics, obstetric and health care service-related characteristics; and media exposure to get information regarding COVID-19 infection; 2) To assess sleep quality; the Pittsburgh Sleep Quality Index (PSQI) was applied. And a global score of > 5 indicates poor sleep quality, and a global score of ≤ 5 indicates good sleep quality. Result: The overall prevalence of poor sleep quality was 62.8%, and was associated with pregnant women aged ≥ 46 years (AOR = 4.27), being in the third trimester (AOR = 2.51), being multigravida (AOR = 2.72), and having co-morbidity (AOR = 3.57). Conclusion: The prevalence of poor sleep quality among pregnant women during the pandemic was found to be high. Advanced maternal age, third trimester pregnancy, being multigravida, and having comorbidity were determinants of poor sleep quality among pregnant women during the Covid-19 pandemic.